Ecologo-Physiological and Caryological Investgations of Some Rare Halophyte Plant Species from Ararat Plain - Ghukasyan, A. G.; Hovakimyan, J. H.; Fayvush, G. M. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
A study of several physiological features of eight plant species has been conducted in order to assess the vulnerability and adaptability to the conditions of salt marshes of the arid region of Armenia. Water regime, intensity of transpiration and photosynthesis, content of plastid pigments have been investigated for the following species: (Merendera sobolifera Fisch. et C. A. Mey., Sphaerophysa salsula DC., Iris musul-manica Fomin, Falcaria falcarioides (Bornm. et H. Wolff) H. Wolff, Microcnemum coralloides (Loscos et Pardo) Font-Quer, Linum barsegianii Gabrielian et Dittr., Frankenia pulverulenta L., Aeluropus littoralis (Gouan) Parl.). The results of the study have indicated that all eight species are well adapted to the highly mineralized soil and groundwater conditions. In this regard, it is revealed that the greatest real threat to the existence of the species is the direct impact of the anthropogenic factor (grazing, arson of vegetation, plowing for fodder plants). As a result of karyological studies, it was revealed that these species are characterized by different ploidy. Ուսումնասիրության համար ընտրվել են ՀՀ Կարմիր գրքում ընդգրկված հազվագյուտ հալոֆիլային 8 բուսատեսակներ` Merendera sobolifera Fisch: et CA Mey., Sphaerophysa salsula DC., Iris musulmanica Fomin, Falcaria falcarioides (Bornm. et H. Wolff) H. Wolff, Microcnemum coralloides (Loscos et Pardo) Font-Quer, Linum barsegianii Gabrielian et Dittr., Frankenia pulveruuslent L., Aeluropus littoralis (Gouan) Parl., որոնք աճում են Արարատ քաղաքի շրջակայքի աղակալած ճահիճներում: Որոշվել են բույսերի ջրային ռեժիմի ցուցանիշները (ազատ և կապված ջուր, ջրային անբավարարություն), պլաստիդային գունանյութերը, և ֆոտոսինթեզի ինտենսիվությունը: Ուսումնասիրության արդյունքները ցույց են տվել, որ բոլոր ութ տեսակներն էլ լավ են հարմարված բարձր հանքայնացված հողի և գրունտային ջրերի պայմաններին: Միաժամանակ պարզվել է, որ տեսակների գոյության ամենամեծ իրական սպառնալիքը անթրոպոգեն գործոնի (արածեցում, բուսականության հրկիզում, կերահանդակների հերկում) ուղղակի ազդեցությունն է: Կարիոլոգիական ուսումնասիրությամբ էլ պարզվել է հալոֆիլ բուսատեսակների պլոիդության առանձնահատկությունները: Для эколого-физиологических исследований выбрано восемь редких галофильных видов: Merendera sobolifera Fisch. et C. A. Mey., Sphaerophysa salsula DC., Iris musulmanica Fomin, Falcaria falcarioides (Bornm. et H. Wolff) H. Wolff, Microcnemum coralloides (Loscos et Pardo) Font-Quer, Linum barsegianii Gabrielian et Dittr., Frankenia pulverulenta L., Aeluropus littoralis (Gouan) Parl., включенных в Красную книгу РА, которые растут на засоленных болотах в окрестностях города Арарат. Определены параметры водного режима растений (свободная и связанная вода, водный дефицит), пластидные пигменты, интенсивность транспирации и фотосинтеза. Результаты исследования показали, что все восемь видов хорошо адаптированы к условиям высокоминерализованной почвы и грунтовых вод. Выявлено, что наибольшую реальную угрозу существованию вида представляет прямое воздействие антропогенного фактора (выпас, поджог растительности, вспашка кормовых угодий). Кариологическими исследованиями выявлены особенности разноплоидности галофильных видов растений.
Keywords: Botany